Magnesium phosphate cement-based protective material capable of resisting biological fouling and application of magnesium phosphate cement-based protective material

By using anti-biologically fouled magnesium phosphate cement-based protective materials on marine photovoltaic power generation equipment, the corrosion and adhesion problems caused by biofouling in the marine environment are solved, and the effect of reducing corrosion risks and extending the equipment life is achieved.

CN119912236AActive Publication Date: 2025-05-02SHANDONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510399131.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2025-05-02
Estimated Expiration
2045-04-01

AI Technical Summary

Technical Problem

Marine photovoltaic power generation equipment is susceptible to biological contamination by microorganisms, algae and shellfish in the marine environment, causing attachments to increase frictional resistance, threaten structural integrity and accelerate corrosion.

Method used

Anti-biological fouling magnesium phosphate cement-based protective material is used, which consists of magnesium phosphate cement, retarder, biological inhibitor and water. The nanocellulose modified by silane coupling agent, stearic acid esterification treatment lignin and modified nano zinc oxide form a biological inhibitor, which improves the self-cleaning ability and anti-fouling performance of the protective layer.

Benefits of technology

It effectively reduces corrosion risks and biological adhesion, extends the life of photovoltaic equipment, reduces frequent cleaning and maintenance, and improves the mechanical strength, structural stability and durability of the protective layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912236A_ABST
    Figure CN119912236A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of cement-based protective materials, and particularly discloses a magnesium phosphate cement-based protective material capable of resisting biological fouling and application of the magnesium phosphate cement-based protective material. The protective material comprises the following components in parts by weight: 100 parts of magnesium phosphate cement, 3-15 parts of a retarder, 1-10 parts of a biological inhibitor and 15-20 parts of water. Wherein the biological inhibitor is prepared from the following raw materials: nano cellulose, lignin, a silane coupling agent, nano zinc oxide, stearic acid and sodium hexametaphosphate in a mass ratio of (1-3): 1: (0.5-1): (0.5-1): (0.5-1): (0.25-0.5). The protective material can effectively improve the self-cleaning capability of a formed protective layer, can effectively reduce the corrosion risk and biological adhesion, prolongs the service life of photovoltaic equipment, and reduces frequent cleaning and maintenance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement-based protective materials, and in particular to a magnesium phosphate cement-based protective material resistant to biological fouling and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Marine photovoltaic power generation refers to the technology of building photovoltaic power stations on the ocean and using the abundant solar energy in the ocean to generate electricity. It has the characteristics of high power generation and does not occupy land resources. Since many equipment of marine photovoltaic power generation technology is built in the ocean, the surface of photovoltaic equipment is susceptible to biological fouling caused by abundant microorganisms and organic matter in the marine environment. At the same time, the surface of photovoltaic equipment can easily become a hotbed for the attachment of microorganisms, algae and shellfish. These attachments will not only increase the friction resistance of the equipment surface, but also threaten its structural integrity, resulting in a significant increase in the corrosion rate of the substrate. If photovoltaic equipment is corroded or damaged due to biological attachment, it may cause the equipment to tilt or become unstable, increasing safety hazards and maintenance costs.

[0004] Traditional anti-corrosion coatings are mainly divided into two types: organic materials and inorganic materials. Among them: organic coatings have problems such as poor weather resistance and volatile organic compound (VOC) release, which makes it difficult to meet the long-term protection needs and environmental protection requirements in the marine environment. Although inorganic coatings (such as cement-based or glass-based protective layers) have good corrosion resistance, they are relatively brittle and are prone to cracking in the complex environment of the ocean due to the impact of waves, sea breezes, and temperature changes, which leads to the infiltration of moisture and corrosive media, resulting in a significant reduction in the anti-corrosion effect. Summary of the invention

[0005] In view of the above problems, the present invention provides a magnesium phosphate cement-based protective material with resistance to biofouling and its application. The protective material can effectively improve the self-cleaning ability of the formed protective layer, effectively reduce the risk of corrosion and biological attachment, extend the life of photovoltaic equipment, and reduce frequent cleaning and maintenance. Specifically, the technical solution of the present invention is as follows.

[0006] First, the present invention provides a magnesium phosphate cement-based protective material for resisting biological fouling, wherein the raw materials include the following components: 100 parts by weight of magnesium phosphate cement, 3-15 parts by weight of retarder, 1-10 parts by weight of biological inhibitor, and 15-20 parts by weight of water. The raw materials for preparing the biological inhibitor include: nanocellulose, lignin, silane coupling agent, nano zinc oxide, stearic acid and sodium hexametaphosphate, and the mass ratios thereof are 1-3:1:0.5-1:0.5-1:0.5-1:0.25-0.5 in sequence.

[0007] Furthermore, the magnesium phosphate cement comprises: dead-burned magnesium oxide and phosphate, and the mass ratio of the two is 1 to 4: 1. Optionally, the phosphate comprises: at least one of ammonium dihydrogen phosphate, potassium dihydrogen phosphate, etc.

[0008] Furthermore, the retarder includes at least one of borax, boric acid, zinc sulfate and the like.

[0009] Furthermore, the silane coupling agent includes one or more of KH-550, KH-560, KH-570, etc.

[0010] Furthermore, the bioinhibitor is prepared by the following method: (1) The nanocellulose is dispersed in an ethanol aqueous solution, and then the silane coupling agent is added. The pH of the system is adjusted to acidic and then heated in a protective atmosphere for reaction. After completion, the solid product is separated, washed and dried to obtain the pre-functionalized nanocellulose for later use.

[0011] (2) dissolving the lignin in ethyl acetate, then adding the stearic acid and part of the nano zinc oxide, subjecting the obtained system to ultrasonic treatment, and then heating the system for reaction. After completion, separating and drying the solid product, the stearic acid esterified lignin is obtained for later use.

[0012] (3) Disperse the remaining nano zinc oxide into water, and then add the sodium hexametaphosphate to carry out stirring reaction. After completion, adjust the pH of the system to alkaline, and then separate the solid product, wash and dry it to obtain the modified nano zinc oxide for standby use.

[0013] (4) Dispersing the pre-functionalized nanocellulose and stearate-treated lignin in an ethanol aqueous solution and then subjecting the solution to ultrasonic treatment, then adding the modified nano zinc oxide to the obtained colloidal suspension, drying the obtained suspension after ultrasonic treatment, and then grinding the obtained solid product to obtain the bioinhibitor.

[0014] Furthermore, in step (1), the ratio of the nanocellulose to the ethanol aqueous solution is 1 g: 30-50 mL. Optionally, the mass fraction of the ethanol aqueous solution is 50-70%.

[0015] Furthermore, in step (1), the pH of the system is adjusted to 5-6, so that the silane coupling agent is hydrolyzed to form activated silanols and evenly distributed, reducing the repolymerization and agglomeration of the silane coupling agent in the solution. Such silanols are more likely to undergo condensation reactions with hydroxyl groups on the surface of the nanocellulose, thereby improving the modification efficiency and stability. Optionally, the pH is adjusted using at least one of acetic acid, citric acid, dilute hydrochloric acid, etc.

[0016] Furthermore, in step (1), the heating temperature is 70-80° C., and the reaction time is 5-7 hours. Optionally, the protective atmosphere includes: any one of nitrogen, argon, etc.

[0017] Furthermore, in step (1), the washing is performed using a solvent such as anhydrous ethanol. In addition, the drying is preferably performed by freeze drying to better maintain the nanostructure integrity of the pre-functionalized nanocellulose.

[0018] Furthermore, in step (2), the mass ratio of the nano zinc oxide to the lignin is 0.02-0.05: 1. Adding a small amount of nano zinc oxide in this step helps to catalyze and promote the esterification reaction between the lignin and stearic acid in the subsequent reaction process.

[0019] Furthermore, in step (2), the ultrasonic treatment time is 15-20 min, the ultrasonic frequency is 20-30 kHz, and the ultrasonic power is 100-150 W, so that the components are fully mixed.

[0020] Furthermore, in step (2), the heating temperature is 90-110° C., and the reaction time is 2-4 hours.

[0021] Furthermore, in step (2), the drying temperature is 50-70° C. and the drying time is 4-8 hours.

[0022] Furthermore, in step (3), the ratio of the nano zinc oxide to water is 1 g: 10-20 mL. Optionally, the stirring reaction time is 1.5-3 hours.

[0023] Furthermore, in step (3), the pH of the system is adjusted to 9-10, so as to promote the deposition of sodium hexametaphosphate on the surface of nano zinc oxide. Optionally, the pH is adjusted using at least one of sodium hydroxide solution, sodium carbonate solution, etc.

[0024] Furthermore, in step (3), the solid product is washed with clean water and then vacuum dried at 60-70° C. for 4-8 hours.

[0025] Furthermore, in step (4), the solid-liquid ratio of the pre-functionalized nanocellulose, stearate-treated lignin and ethanol aqueous solution is 1 g: 20-50 mL. Optionally, the mass fraction of the ethanol aqueous solution is 60-70%.

[0026] Furthermore, step (4) further includes the step of adding a silane coupling agent to the colloidal suspension, thereby accelerating silane coupling, improving the dispersibility of nano zinc oxide, avoiding agglomeration, improving antibacterial properties, enhancing the interfacial compatibility of nano cellulose and lignin, and preventing component stratification to ensure final uniform solidification. Optionally, the mass fraction of the silane coupling agent in the colloidal suspension is 1 to 1.5%. The silane coupling agent includes one or more of KH-550, KH-560, KH-570, etc.

[0027] Furthermore, in step (4), the ultrasonic treatment time is 15-25 min, the ultrasonic frequency is 20-30 kHz, and the ultrasonic power is 100-150 W.

[0028] Furthermore, in step (4), the particle size of the bio-inhibitor is 60-200 mesh.

[0029] Secondly, the present invention discloses a method for preparing the magnesium phosphate cement-based protective material that resists biological fouling, comprising the steps of: uniformly mixing the magnesium phosphate cement, retarder, bio-inhibitor and water. When in use, the obtained protective material is applied to the surface of a substrate, and a protective layer is formed after solidification. Optionally, the thickness of the protective layer is 0.5-1 mm.

[0030] Finally, the present invention provides the application of the anti-biofouling magnesium phosphate cement-based protective material in the fields of construction engineering, marine engineering, water conservancy and hydropower engineering, etc.

[0031] Compared with the prior art, the present invention has at least the following beneficial technical effects: The protective layer formed by the anti-biofouling magnesium phosphate cement-based protective material of the present invention has good self-cleaning ability, improves the anti-fouling performance, and effectively reduces the risk of corrosion and biological attachment. To this end, the present invention first uses a silane coupling agent to modify the nanocellulose to form pre-functionalized nanocellulose. In this process, the silane coupling agent reacts with the hydroxyl groups on the surface of the nanocellulose to form Si-O-C bonds, and at the same time, the surface of the nanocellulose is provided with organic functional groups, thereby improving the dispersibility of the nanocellulose in the organic phase and improving the hydrophobicity. In addition, the silane coupling agent can also form chemical bonds or functional groups (such as amino or alkyl) with physical adsorption with the magnesium phosphate cement matrix, thereby improving the bonding strength between the nanocellulose and the protective material matrix, making it uniformly dispersed in the protective material, and enhancing the stability and durability of the protective material. Secondly, the present invention modifies lignin by stearic acid, because the direct incorporation of lignin into the magnesium phosphate cement system will make it difficult to disperse uniformly and reduce the hydrophobicity of the protective material. The present invention can effectively shield the polar groups of lignin by grafting stearic acid onto the hydroxyl groups of lignin, so that the surface of the modified lignin carries a long-chain alkyl group. This structure can form a low surface energy molecular layer on the surface of the protective material, effectively reduce the contact angle, and provide the protective material with significant hydrophobic properties while ensuring environmental protection, thereby preventing water from penetrating, reducing microbial attachment, and improving the anti-fouling ability of the protective material. Again, the present invention uses sodium hexametaphosphate to perform surface modification on nano zinc oxide, which effectively improves the dispersibility and stability of nano zinc oxide, and makes the nano zinc oxide evenly distributed in the magnesium phosphate matrix to avoid agglomeration. Finally, the present invention combines the obtained pre-functionalized nano cellulose, stearic acid esterified lignin and modified nano zinc oxide to form a bio-inhibitor. Since the surfaces of nano cellulose, lignin and nano zinc oxide are all functionally modified, they can better combine with the magnesium phosphate cement matrix to form an evenly distributed anti-fouling layer, thereby improving the overall protective performance.

[0032] After the bio-inhibitor of the present invention is added to the protective material, the nanocellulose has the characteristics of high specific surface area and abundant hydroxyl groups, and the Mg in magnesium phosphate cement is used to inhibit the growth of the bio-inhibitor. 2+Ionic action generates hydrogen bond complexes, which enhances the mechanical strength, structural stability, wear resistance and impact resistance of the protective layer. The lignin can not only improve the corrosion resistance of the protective layer, but also help to inhibit biological pollution in the marine environment. The silane coupling agent can react with the hydroxyl groups of nanocellulose and lignin to construct a cross-linked network, significantly improving the mechanical properties and durability of the protective layer. At the same time, the siloxane groups in the silane coupling agent react with the hydroxyl groups in the magnesium phosphate cement to form a silicon-oxygen-metal ion bonding structure, thereby helping to enhance the bonding force with the protective material matrix and improve the interface stability. In addition, it also helps to improve the dispersibility of nano zinc oxide, improve the bonding strength with the matrix, and enhance the stability and durability of the protective material. The epoxy group of the silane coupling agent reacts with the PO provided by the magnesium phosphate cement. 4 3- The ions react to form a chemical cross-linking structure, further enhancing the corrosion resistance of the protective layer. The amino groups of the silane coupling agent react with the Mg provided by the magnesium phosphate cement. 2+ The coordination between the ions will form a stable complex, which enhances the adhesion of the protective layer. 4 3- Ions can also interact with Mg in the magnesium phosphate matrix 2+ Ion reaction forms a denser phosphate precipitation layer, thereby further enhancing the corrosion resistance and mechanical strength of the protective layer. At the same time, the nano zinc oxide modified by sodium hexametaphosphate has a broad-spectrum antibacterial and anti-biological attachment effect, and can gradually release Zn²⁺ ions in the water environment. These ions inhibit the metabolic activity of microorganisms by combining with thiol groups in microbial cells, thereby effectively inhibiting the growth of attached algae, bacteria and other marine microorganisms. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein: Figure 1 This is a sample picture of the bioinhibitor prepared in Example 1 below.

[0034] Figure 2 This is a sample picture of the magnesium phosphate cement-based protective material prepared in the following Example 1.

[0035] Figure 3 This is a bonding strength test chart of the magnesium phosphate cement-based protective material prepared in the following Example 1.

[0036] Figure 4 This is a hydrophobicity test chart of the magnesium phosphate cement-based protective material prepared in the following Example 1.

[0037] Figure 5 This is a sample picture of the bioinhibitor prepared in Example 2 below.

[0038] Figure 6 This is a sample picture of the magnesium phosphate cement-based protective material prepared in the following Example 2.

[0039] Figure 7 This is a bonding strength test chart of the magnesium phosphate cement-based protective material prepared in the following Example 2.

[0040] Figure 8 This is a hydrophobicity test chart of the magnesium phosphate cement-based protective material prepared in the following Example 2. DETAILED DESCRIPTION

[0041] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer.

[0042] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention.

[0043] Example 1 A preparation method of a magnesium phosphate cement-based protective material that resists biofouling comprises the following steps: (1) Prepare the raw materials in the following proportions: nanocellulose, lignin, silane coupling agent (KH-550), nano zinc oxide, stearic acid and sodium hexametaphosphate, with the mass ratios being 2:1:0.7:0.8:0.55:0.4, respectively.

[0044] (2) The nanocellulose is mixed with a 50% ethanol aqueous solution at a ratio of 1 g:50 mL, and then the silane coupling agent is added, and acetic acid is added to adjust the pH of the system to 5. Then, the mixture is heated to 75° C. in a nitrogen atmosphere for 6 hours. After completion, the solid product is filtered out, washed with anhydrous ethanol, and freeze-dried to obtain pre-functionalized nanocellulose for later use.

[0045] (3) The lignin is dissolved in ethyl acetate, and then the stearic acid and nano zinc oxide are added, and the mass ratio of the nano zinc oxide to the lignin is 0.03:1. The obtained system is then subjected to ultrasonic treatment for 15 minutes (ultrasonic frequency is 30 kHz, ultrasonic power is 100 W), and then heated to 100° C. for reaction for 2.5 hours, and then the solid product is filtered out and dried at 70° C. for 4 hours to obtain stearic acid esterified lignin for later use.

[0046] (4) The remaining nano zinc oxide and water were mixed in a ratio of 1 g: 20 mL, and then ultrasonically dispersed for 30 minutes, and then the sodium hexametaphosphate was added and stirred for reaction for 1.5 hours. After completion, sodium hydroxide solution was added to adjust the pH of the system to 9, and then the solid product was filtered out, washed with clean water, and vacuum dried at 60° C. for 7 hours to obtain modified nano zinc oxide for later use.

[0047] (5) The pre-functionalized nanocellulose and stearate-treated lignin of this embodiment are dispersed in a 60% ethanol aqueous solution at a solid-liquid ratio of 1g:35mL, and then ultrasonically treated for 15 minutes (ultrasonic frequency of 30kHz, ultrasonic power of 100W). Then, the modified nano zinc oxide of this embodiment is added to the obtained colloidal suspension, and a silane coupling agent (KH-550) is added to form a suspension containing 1.0wt.% of the silane coupling agent. The suspension is ultrasonically treated for 15 minutes (ultrasonic frequency of 30kHz, ultrasonic power of 100W), and then the obtained suspension is spray-dried. The obtained solid product is then placed in a ball mill for grinding for 2 hours to obtain a bio-inhibitor with a particle size distribution between 50 and 100nm, such as Figure 1 shown.

[0048] (6) Take the following raw materials: 100 parts by weight of magnesium phosphate cement, 9 parts by weight of borax, 6.5 parts by weight of the biological inhibitor in this embodiment, and 17 parts by weight of water. The magnesium phosphate cement is prepared by mixing dead-burned magnesium oxide and potassium dihydrogen phosphate in a mass ratio of 3:1. Mix the above raw materials and stir for 2 minutes to obtain a magnesium phosphate cement-based protective material, such as Figure 2 shown.

[0049] Performance test: (1) The material prepared in the example was coated on the surface of a Q235 steel plate to form a protective layer with a thickness of 1 mm, and then the salt spray resistance of the protective layer was tested using a YWX / Q-250 salt spray tester. (2) The protective material prepared in this example was tested for bonding strength according to GB / T-5210-2006 "Adhesion test for paint and varnish by pull-off method" (such as Figure 3 (3) The hydrophobicity of the protective material is tested using a Chengde Dingsheng JY-82C video contact angle tester (as shown). Figure 4 The test results are shown in Table 1 below: Table 1 .

[0050] Example 2 A preparation method of a magnesium phosphate cement-based protective material that resists biofouling comprises the following steps: (1) Prepare the raw materials in the following proportions: nanocellulose, lignin, silane coupling agent (KH-570), nano zinc oxide, stearic acid and sodium hexametaphosphate, with the mass ratios being 1:1:0.5:0.5:0.5:0.25, respectively.

[0051] (2) The nanocellulose is mixed with an ethanol aqueous solution having a mass fraction of 70% at a ratio of 1 g:30 mL, and then the silane coupling agent is added, and citric acid is added to adjust the pH of the system to 6. Then, the mixture is heated to 80° C. in a nitrogen atmosphere for reaction for 5 hours. After completion, the solid product is filtered out, washed with anhydrous ethanol, and freeze-dried to obtain pre-functionalized nanocellulose for later use.

[0052] (3) The lignin is dissolved in ethyl acetate, and then the stearic acid and nano zinc oxide are added, and the mass ratio of the nano zinc oxide to the lignin is 0.02:1. The obtained system is then subjected to ultrasonic treatment for 20 minutes (ultrasonic frequency is 20 kHz, ultrasonic power is 150 W), and then heated to 90°C for reaction for 4 hours, and then the solid product is filtered out and dried at 50°C for 8 hours to obtain stearic acid esterified lignin for later use.

[0053] (4) The remaining nano zinc oxide and water were mixed in a ratio of 1 g: 10 mL and then ultrasonically dispersed for 30 minutes, and then the sodium hexametaphosphate was added and stirred for reaction for 2 hours. After completion, sodium hydroxide solution was added to adjust the pH of the system to 10, and then the solid product was filtered out, washed with clean water, and vacuum dried at 70° C. for 4 hours to obtain modified nano zinc oxide for later use.

[0054] (5) The pre-functionalized nanocellulose and stearate-treated lignin of this embodiment are dispersed in a 70% ethanol aqueous solution at a solid-liquid ratio of 1g:50mL, and then ultrasonically treated for 20 minutes (ultrasonic frequency of 20kHz, ultrasonic power of 150W). Then, the modified nano zinc oxide of this embodiment is added to the obtained colloidal suspension, and a silane coupling agent (KH-570) is added to form a suspension containing 1.3wt.%, which is ultrasonically treated for 20 minutes (ultrasonic frequency of 25kHz, ultrasonic power of 110W), and then the obtained suspension is spray-dried, and then the obtained solid product is placed in a ball mill for grinding for 2 hours to obtain a bioinhibitor with a particle size distribution between 80 and 150nm, such as Figure 5 shown.

[0055] (6) Take the following raw materials: 100 parts by weight of magnesium phosphate cement, 15 parts by weight of boric acid, 10 parts by weight of the biological inhibitor in this embodiment, and 20 parts by weight of water. The magnesium phosphate cement is prepared by mixing dead-burned magnesium oxide and potassium dihydrogen phosphate in a mass ratio of 4:1. Mix the above raw materials and stir for 2 minutes to obtain a magnesium phosphate cement-based protective material, such as Figure 6 shown.

[0056] The same method as in Example 1 was used to measure the salt spray resistance, bonding strength, and contact angle (such as Figure 8 The test was carried out as shown in Table 2 below, and the results are shown in Table 2 below, indicating that the protective material has excellent hydrophobic properties: Table 2 .

[0057] Example 3 A preparation method of a magnesium phosphate cement-based protective material that resists biofouling comprises the following steps: (1) Prepare the raw materials in the following proportions: nanocellulose, lignin, silane coupling agent (KH-560), nano zinc oxide, stearic acid and sodium hexametaphosphate, with the mass ratios being 3:1:1:1:1:0.5 in that order.

[0058] (2) The nanocellulose is mixed with an ethanol aqueous solution having a mass fraction of 60% at a ratio of 1 g:45 mL, and then the silane coupling agent is added, and dilute hydrochloric acid is added to adjust the pH of the system to 5. Then, the mixture is heated to 70° C. in a nitrogen atmosphere for reaction for 7 hours. After completion, the solid product is filtered out, washed with anhydrous ethanol, and freeze-dried to obtain pre-functionalized nanocellulose for later use.

[0059] (3) The lignin is dissolved in ethyl acetate, and then the stearic acid and nano zinc oxide are added, and the mass ratio of the nano zinc oxide to the lignin is 0.05:1. The obtained system is then subjected to ultrasonic treatment for 20 minutes (ultrasonic frequency is 30 kHz, ultrasonic power is 140 W), and then heated to 110° C. for reaction for 2 hours, and then the solid product is filtered out and dried at 60° C. for 5 hours to obtain stearic acid esterified lignin for later use.

[0060] (4) The remaining nano zinc oxide and water were mixed in a ratio of 1 g: 15 mL, and then ultrasonically dispersed for 30 minutes, and then the sodium hexametaphosphate was added and stirred for reaction for 3 hours. After completion, sodium carbonate solution was added to adjust the pH of the system to 10, and then the solid product was filtered out, washed with clean water, and vacuum dried at 60° C. for 8 hours to obtain modified nano zinc oxide for later use.

[0061] (5) The pre-functionalized nanocellulose and stearate-treated lignin of this embodiment were dispersed in a 65% ethanol aqueous solution at a solid-liquid ratio of 1g:20mL, and then ultrasonically treated for 25 minutes (ultrasonic frequency of 20kHz, ultrasonic power of 150W). Then, the modified nano zinc oxide of this embodiment was added to the obtained colloidal suspension, and a silane coupling agent (KH-560) was added to form a suspension containing 1.5wt.% of the silane coupling agent, which was ultrasonically treated for 25 minutes (ultrasonic frequency of 20kHz, ultrasonic power of 150W), and then the obtained suspension was spray-dried, and then the obtained solid product was placed in a ball mill for grinding for 3 hours to obtain a bio-inhibitor with a particle size distribution between 100 and 200nm.

[0062] (6) Take the following raw materials: 100 parts by weight of magnesium phosphate cement, 3 parts by weight of borax, 1 part by weight of the bio-inhibitor of this embodiment, and 15 parts by weight of water. The magnesium phosphate cement is prepared by mixing dead-burned magnesium oxide and diammonium phosphate in a mass ratio of 1:1. Mix the above raw materials and stir for 2 minutes to obtain a magnesium phosphate cement-based protective material.

[0063] The salt spray resistance, bonding strength and contact angle of the magnesium phosphate cement-based protective material prepared in this embodiment were tested by the same method as in the above-mentioned embodiment 1. The results are shown in Table 3 below, indicating that the protective material has excellent hydrophobic properties: Table 3 .

[0064] Example 4 Preparation of a magnesium phosphate cement-based protective material that resists biological fouling, the same as the above-mentioned Example 1, the difference is that the biological inhibitor of this example is prepared by the following method: the unmodified nanocellulose and the stearate-treated lignin of Example 1 are dispersed in a 60% ethanol aqueous solution according to a solid-liquid ratio of 1g:35mL, and then ultrasonically treated for 15min (ultrasonic frequency of 30kHz, ultrasonic power of 100W). Then, the modified nano zinc oxide of Example 1 is added to the obtained colloidal suspension, and a silane coupling agent (KH-550) is added to form a suspension containing 1.0wt.% of the silane coupling agent, which is ultrasonically treated for 15min (ultrasonic frequency of 30kHz, ultrasonic power of 100W), and then the obtained suspension is spray-dried, and then the obtained solid product is placed in a ball mill for grinding for 2 hours to obtain a biological inhibitor with a particle size distribution between 50 and 100nm.

[0065] The salt spray resistance, bonding strength and contact angle of the magnesium phosphate cement-based protective material prepared in this embodiment were tested by the same method as in the above embodiment 1. The results are shown in Table 4 below: Table 4 .

[0066] Example 5 Preparation of a magnesium phosphate cement-based protective material that resists biological fouling, the same as the above-mentioned Example 2, the difference is that the biological inhibitor of this example is prepared by the following method: the pre-functionalized nanocellulose and the unmodified lignin of Example 2 are dispersed in a 70% ethanol aqueous solution according to a solid-liquid ratio of 1g:50mL, and then ultrasonically treated for 20 minutes (ultrasonic frequency of 20kHz, ultrasonic power of 150W). Then, the modified nano zinc oxide of Example 2 is added to the obtained colloidal suspension, and a silane coupling agent (KH-570) is added to form a suspension containing 1.3wt.% of the silane coupling agent, which is ultrasonically treated for 20 minutes (ultrasonic frequency of 25kHz, ultrasonic power of 110W), and then the obtained suspension is spray-dried, and then the obtained solid product is placed in a ball mill for grinding for 2 hours to obtain a biological inhibitor with a particle size distribution between 80 and 150nm.

[0067] The salt spray resistance, bonding strength and contact angle of the magnesium phosphate cement-based protective material prepared in this embodiment were tested by the same method as in the above embodiment 1. The results are shown in Table 5 below: Table 5 .

[0068] Example 6 The preparation of a magnesium phosphate cement-based protective material that resists biological fouling is the same as that of the above-mentioned Example 3, except that the bioinhibitor of this example is prepared by the following method: (1) The remaining nano zinc oxide was mixed with water in a ratio of 1 g: 15 mL and then ultrasonically dispersed for 30 min. Then, sodium carbonate solution was added to adjust the pH of the system to 10. The solid product was filtered out and washed with clean water. Then, it was vacuum dried at 60° C. for 8 hours to obtain modified nano zinc oxide for later use.

[0069] (2) The pre-functionalized nanocellulose and stearate-treated lignin of Example 3 were dispersed in a 65% ethanol aqueous solution at a solid-liquid ratio of 1g:20mL, and then ultrasonically treated for 25 minutes (ultrasonic frequency of 20kHz, ultrasonic power of 150W). Then, the modified nano zinc oxide prepared in this example was added to the obtained colloidal suspension, and a silane coupling agent (KH-560) was added to form a suspension containing 1.5wt.% of the silane coupling agent, which was ultrasonically treated for 25 minutes (ultrasonic frequency of 20kHz, ultrasonic power of 150W), and then the obtained suspension was spray-dried, and then the obtained solid product was placed in a ball mill for grinding for 3 hours to obtain a bio-inhibitor with a particle size distribution between 100 and 200nm.

[0070] The salt spray resistance, bonding strength and contact angle of the magnesium phosphate cement-based protective material prepared in this embodiment were tested by the same method as in the above embodiment 1. The results are shown in Table 6 below: Table 6 .

[0071] Example 7 Preparation of a magnesium phosphate cement-based protective material that resists biological fouling, the same as the above-mentioned Example 2, the difference is that the biological inhibitor of this example is prepared by the following method: the stearic acid esterified lignin prepared in Example 2 is dispersed in an ethanol aqueous solution with a mass fraction of 70% according to a solid-liquid ratio of 1g:25mL, and then ultrasonically treated for 20 minutes (ultrasonic frequency is 20kHz, ultrasonic power is 150W). Then, the modified nano zinc oxide prepared in Example 2 is added to the obtained colloidal suspension, and a silane coupling agent (KH-570) is added to form a suspension containing 1.3wt.% of the silane coupling agent, which is ultrasonically treated for 20 minutes (ultrasonic frequency is 25kHz, ultrasonic power is 110W), and then the obtained suspension is spray-dried, and then the obtained solid product is placed in a ball mill for grinding for 2 hours to obtain a biological inhibitor with a particle size distribution between 80 and 150nm.

[0072] The salt spray resistance, bonding strength and contact angle of the magnesium phosphate cement-based protective material prepared in this embodiment were tested by the same method as in the above embodiment 1. The results are shown in Table 7 below: Table 7 .

[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still repair the technical solutions recorded in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any repair, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A magnesium phosphate cement-based protective material resistant to biofouling, characterized in that: The raw materials of the protective material include the following components: 100 parts by weight of magnesium phosphate cement, 3 to 15 parts by weight of retarder, 1 to 10 parts by weight of bio-inhibitor, and 15 to 20 parts by weight of water; wherein: The raw materials for preparing the bioinhibitor include: nano cellulose, lignin, silane coupling agent, nano zinc oxide, stearic acid and sodium hexametaphosphate, and the mass ratios thereof are 1-3:1:0.5-1:0.5-1:0.5-1:0.25-0.5 in sequence.

2. The anti-biofouling magnesium phosphate cement-based protective material according to claim 1, characterized in that: The bioinhibitor is prepared by the following method: (1) dispersing the nanocellulose in an ethanol aqueous solution, then adding the silane coupling agent, adjusting the pH of the system to acidic, and then heating the system in a protective atmosphere for reaction; after completion, separating the solid product, washing it, and drying it to obtain the pre-functionalized nanocellulose for later use; (2) dissolving the lignin in ethyl acetate, then adding the stearic acid and a portion of the nano zinc oxide, subjecting the obtained system to ultrasonic treatment, and then heating the system for reaction. After completion, separating and drying the solid product, the stearic acid esterified lignin is obtained for later use; (3) dispersing the remaining nano zinc oxide into water, and then adding the sodium hexametaphosphate to carry out stirring reaction; after completion, adjusting the pH of the system to alkaline, and then separating the solid product, washing and drying to obtain modified nano zinc oxide for standby use; (4) The pre-functionalized nanocellulose and stearate-treated lignin are dispersed in an ethanol aqueous solution and then ultrasonically treated; then the modified nano zinc oxide is added to the obtained colloidal suspension, the obtained suspension is dried after ultrasonic treatment, and then the obtained solid product is ground to obtain the bioinhibitor.

3. The anti-biofouling magnesium phosphate cement-based protective material according to claim 2, characterized in that: In step (1), the ratio of the nanocellulose to the ethanol aqueous solution is 1 g: 30-50 mL; Alternatively, in step (1), the mass fraction of the ethanol aqueous solution is 50-70%; Alternatively, in step (1), the pH of the system is adjusted to 5-6; or, the pH is adjusted using at least one of acetic acid, citric acid, and dilute hydrochloric acid; Alternatively, in step (1), in step (1), the heating temperature is 70-80° C., and the reaction time is 5-7 hours.

4. The anti-biofouling magnesium phosphate cement-based protective material according to claim 2, characterized in that: In step (2), the mass ratio of the nano zinc oxide to lignin is 0.02-0.05:1; Alternatively, in step (2), the ultrasonic treatment time is 15-20 min, the ultrasonic frequency is 20-30 kHz, and the ultrasonic power is 100-150 W; Alternatively, in step (2), the heating temperature is 90-110° C., and the reaction time is 2-4 hours; Alternatively, in step (2), the drying temperature is 50-70° C. and the drying time is 4-8 hours.

5. The anti-biofouling magnesium phosphate cement-based protective material according to claim 2, characterized in that: In step (3), the ratio of nano zinc oxide to water is 1 g: 10-20 mL; Alternatively, in step (3), the stirring reaction time is 1.5 to 3 hours; Alternatively, in step (3), the pH of the system is adjusted to 9-10, thereby promoting the deposition of phosphate on the surface of nano zinc oxide; Alternatively, in step (3), at least one of a sodium hydroxide solution and a sodium carbonate solution is used to adjust the pH; Alternatively, in step (3), the solid product is washed with clean water and then vacuum dried at 60-70° C. for 4-8 hours.

6. The anti-biofouling magnesium phosphate cement-based protective material according to claim 2, characterized in that: In step (4), the solid-liquid ratio of the pre-functionalized nanocellulose, stearate-treated lignin and ethanol aqueous solution is 1 g: 20-50 mL; Alternatively, in step (4), the mass fraction of the ethanol aqueous solution is 60-70%; Alternatively, in step (4), the ultrasonic treatment time is 15 min, the ultrasonic frequency is 20-30 kHz, and the ultrasonic power is 100-150 W; Alternatively, in step (4), the bio-inhibitor has a fineness of 60-200 mesh.

7. The anti-biofouling magnesium phosphate cement-based protective material according to any one of claims 2 to 6, characterized in that: Step (4) also includes the step of adding a silane coupling agent into the colloidal suspension.

8. The anti-biofouling magnesium phosphate cement-based protective material according to claim 7, characterized in that: The mass fraction of the silane coupling agent in the colloidal suspension is 1-1.5%; Alternatively, the silane coupling agent includes one or more of KH-550, KH-560, and KH-570.

9. The anti-biofouling magnesium phosphate cement-based protective material according to any one of claims 1 to 6, characterized in that: The magnesium phosphate cement comprises: dead-burned magnesium oxide and phosphate, the mass ratio of the two being 1-4:1; Alternatively, the phosphate includes: at least one of ammonium dihydrogen phosphate and potassium dihydrogen phosphate; Alternatively, the retarder includes: at least one of borax, boric acid, and zinc sulfate; Alternatively, the silane coupling agent includes one or more of KH-550, KH-560, and KH-570.

10. Application of the anti-biofouling magnesium phosphate cement-based protective material according to any one of claims 1 to 9 in the fields of construction engineering, marine engineering, water conservancy and hydropower engineering.

Citation Information

Patent Citations

  • Retarding water-resistant agent suitable for magnesium phosphate cement system

    CN115286275A

  • Rapid pavement repairing mortar compounded with magnesium cement and alkali-activated slag and preparation method of rapid pavement repairing mortar

    CN117800702A

  • Phosphorus-magnesium cement-based anti-corrosion and anti-permeability coating material as well as preparation method and application thereof

    CN118063186A

  • Preparation method and application of waterproof impervious magnesium phosphate cement-based material

    CN118206354A